Comparative nephrotoxic effect on rats of different pathogens - Levitsky, A. P.; Stepan, V. T.; Pustovoit, P. I. (Journal of Education, Health and Sport, 2020)
Aim. Compare the nephrotoxicity of different pathogens. Methods. Nephrotoxicity was assessed in rats treated with the following pathogens: hydrazine sulfate, prednisolone, cyclophosphamide, lincomycin and lipopolysaccharide, according to the degree of increase in biochemical markers of inflammation: elastase activity and malondialdehyde (MDA) content. Result. A significant increase in the level of both inflammatory markers in the kidneys was established, the most pronounced under the influence of hydrazine sulfate. The recalculation of the percentage increase in the level of markers per 1 mg of the pathogen (specific pro-inflammatory activity, SPIA) showed the highest SPIA in lipopolysaccharide, especially after oral applications, exceeding SPIA for hydrazine sulfate by a factor of thousands. Conclusion. The pro-inflammatory effect on kidneys of many non-microbial toxicants can be realized through the formation of lipopolysaccharide by lysis of gram-negative bacteria.